The effect of tea polyphenols on biogenic amines and free amino acids in bighead carp (Aristichthys nobilis) fillets during frozen storage. (October 2021) - Dai, Wangli; Gu, Saiqi; Xu, Mingjiang; Wang, Wenjie; Yao, Hongzheng; Zhou, Xuxia; Ding, Yuting
Abstract: The effect of dipping frozen bighead carp fillets in tea polyphenols (TPs) on biogenic amines (BAs) and free amino acids (FAAs) was examined to investigate the inhibition of BA formation in fish during frozen storage. The TP dipping treatment effectively retarded the formation of BAs and the loss of FAAs in the bighead carp fillets during frozen storage. In particular, the BA content in the TP-treated samples was 30%–46% lower than that of the control samples. Additionally, the pH and total volatile basic nitrogen (TVB-N) value in the TP treated samples decreased by 3%–5% and 14%–22%, respectively. Lower storage temperatures contributed to reducing the above attribute values. Redundancy analysis (RDA) indicated positive correlations between histidine and histamine and between phenylalanine and 2-phenylethylamine. However, there were negative correlations between other BAs, such as cadaverine, tyramine, spermidine and spermine, and their precursor FAAs. This study provides updated information on the associations between BAs and FAAs in fish during frozen storage, and it introduced an advanced protocol for improving the freshness and safety of aquatic products during frozen storage. Graphical abstract: Image 1 Highlights: Tea polyphenols could effectively reduce the formation of biogenic amines. Correlations between biogenic amines and free amino acids were revealed. Histidine-abundant fish contributed to more histamine accumulation during storage. Dipping in a tea polyphenols solution improved fish safety.